Targeting Breast Cancer in Diabetic Mice Using a Combination of Thymoquinone and Metformin - Aboulqassim, Naeimah S. Sulayman; Talib, Wamidh H. (Natural Products Journal, The, 2023)
Objective: The aim of our study was to assess thymoquinone (TQ) as a combination therapy with metformin (MT) against breast cancer in diabetic tumor-bearing mice. Methods: The antiproliferative activities of TQ and MET and their combination were tested against three breast cancer cell lines (EMT6/P, T47D, MDA-MB-231) using an MTT assay. We used the isobolographic method to calculate the combination index (CI). Balb/C mice were implanted with EMT6/P cells and diabetes was induced using Streptozotocin (STZ). The antitumor activity was assessed for TQ and MET and their combination in vivo. The antiangiogenic activity and apoptosis induction ability of TQ and MET were estimated using ELISA kits. To estimate the liver and kidney functions, aspartate transaminase (AST), alanine transaminase (ALT) levels, and creatinine were detected in serum samples using standard kits. The impact of the TQ and MET combination on reducing blood glucose levels was measured daily using a glucometer. Results: Synergistic anticancer effect was observed between TQ and MET. The combination of TQ and MET caused a significant reduction in tumor size (p-value <0.05) with a high cure percentage of (71.42%) and lower blood glucose levels. The combination therapy induces apoptosis, inhibits angiogenesis, and causes tumor regression. Moreover, no significant effect was observed in the serum levels of AST, ALT, and creatinine, as the values were very close to the normal ones. Conclusion: The combination of TQ and MET is considered a promising anticancer therapy to treat breast cancer induced by diabetes and nondiabetes mice. This combination possesses antiproliferative activity, anti-hyperglycemic activity, inhibits angiogenesis and induces apoptosis. Furthermore, this combination demonstrated low toxicity.
Keywords: combination therapy